Impact of Training and Development on Job Satisfaction and Job Performance with Moderating Effect of Person Job Fit - Muhammad Yar Khan; Jawaria Mushtaq; Shumaila Naz (UW Journal of Management Sciences, 2022)
Purpose: The main motive behind the study is to find out the impact of training and development on the satisfaction level as well as their performance on their respective jobs. The factor of personal job has been employed as the moderator in the study. Design and Methodology: As a sample of 450 respondents was taken from different Foundation Colleges. Findings: The results revealed the positive influence of training and development on individual performance and the important role it plays in improving the gratification level of an employee with his job. Furthermore, person job fit variable acts as an active moderator among the relationships. This work leads potentially to the establishment of a sense of training and development awareness through past experiences in different institutes. Implications: This study also provides insights regarding the comparison of these variables. Future researchers may involve the survey strategy for this study.